Parental Reflective Functioning and Its Association With Parenting Behaviors in Infancy and Early Childhood: A Systematic Review - Stuhrmann, Lydia Yao; Göbel, Ariane; Bindt, Carola; Mudra, Susanne (Frontiers in Psychology, 2022)
Background: Parental reflective functioning (PRF) refers to parents’ mental capacity to understand their own and their children’s behaviors in terms of envisioned mental states. As part of a broader concept of parental mentalization, PRF has been identified as one of the central predictors for sensitive parenting. However, the unique contribution of PRF to the quality of various parenting behaviors has not yet been addressed systematically. Thus, the present article provides a systematic overview of current research on the associations between PRF or its sub-dimensions and observed parenting behaviors in infancy and early childhood while considering the influence of contextual factors. Methods: The review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Systematic searches were carried out in five electronic databases. The eligibility and methodological quality of the identified studies were assessed using pre-defined criteria and a standardized checklist. Results: Sixteen studies with moderate to high quality on a total of 15 parenting behaviors were included, the majority of which examined positive parenting behaviors, while negative parenting behaviors were rarely investigated. Most of the associations indicated a positive effect of PRF on parenting behavior, with mostly small-sized effects. The strength and direction of the associations varied depending on the dimensionality of PRF, observation settings, sample types, socioeconomic factors, and cultural background. Moreover, five assessment instruments for PRF and ten observation instruments for parenting behaviors were identified. Conclusion: In summary, PRF has shown a positive association with parenting quality. However, its complex interaction with further contextual factors emphasizes the need for differentiation of PRF dimensions and the consideration of the observation settings, assessment time points, psychosocial risks, and sample types in observational as well as intervention studies. Further high-quality studies with multivariate analyses and diverse study settings are required.